Studying the Effect of Lactobacillus fermentum on Arc and CREB Genes Expression of Involved in The Memory of Alzheimer\'s Rats - Elnaz Mogaddam; Maryam Tehranipur; Mahboobeh Nakhaei Moghaddam; Khadijeh Nejad Shahrokhabadi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2023)
Introduction: Alzheimer's disease is a common progressive neurogenerative disease that leads to dementia and destruction of brain cells, especially in areas related to learning and memory such as the hippocampus. The role of the Arc gene in synaptic flexibility and memory consolidation has been proven and its expression is strongly influenced by neuronal activity. The aim of this study was to investigate the effect of Lactobacillus fermentum on the expression of Arc (effective in synaptic flexibility and memory consolidation) and CREB (effective in stabilizing synaptic changes during learning) genes, involved in the memory of Alzheimer's rats. Material & ethods: In this study that was conducted in 2019, 30 male Wistar rats were divided into 5 groups (control, Alzheimer and 3 groups as treatment). In the treatment groups, simultaneously with induction of Alzheimer by stereotaxic method with streptozotocin, supernatant of Lactobacillus fermentum PTCC 1744 in MRS broth with doses of 108, 107, and 106 cfu/ml was injected intraperitoneally for 21 days. After RNA extraction from hippocampus samples, cDNA was synthesized and the expression of the genes was evaluated by real-time PCR and LinReg PCR software. Findings: The data showed an increase in gene expression of Arc and CREB in the treatment groups with a dose of 106 cfu/ml compared to the Alzheimer's group and the difference was significant (P <0.001). Discussion & conclusion: Extracellular compounds of L. fermentum may inhibit the progression of neuronal lesions due to their antioxidant and anti-inflammatory effects and may be effective in improving Alzheimer's.